HAK KEKAYAAN INTELEKTUAL: Selayang Pandang Tentang Hak Cipta, Paten dan Disain Industri - F. Mursiati SH. (Ars: Jurnal Seni Rupa dan Desain, 2006)
The Indonesian terms "HAKI" or "IIKI" which are equivalent to the English term IntellectualProperty Rights are considered as a new idea for Indonesians Nevertheless, the Indonesians are familiarwith the terms "Hak Cipta" "Paten" and '’Disain". Even though it is common that those words arcapplied in a sentence at the same time, e.g. 'mematenkan ciptaan" (the u>ord "paten" and "cipta '),"disain yang sudah dipatenkan"(the words "disain"and "paten"), it is a complete mistake.A creator as the subject o f "Hak Cipta " (copyright) is someone or a group o f people loho createssomething in afield o f science, art, and literature because ofhidfher/their inspiration.An invertor, the subject o f "Paten" f Pa tent), is an individu or a group o f people who conducts anactivity o f solving a problem in technology. It can beaprocess orproduct.A designer is someone or a group o f people who produces an industrial design. It can be in a form o fshape, configuration, or composition (o f lines and colors, or the combination o f lines and colors) or thecombination o f them in a form o f 3-dimertsior. or 2-dimension that gives esthetic impression and can berealized in a 3-dimensional o< 2-dimensional pattern. It can also be used to producc a product, object, orindustrial commodity and handycraft.Key words: Intellectual Property Rights (IPR) HKI, copyright (Hak Cipta), Patent (Paten;,Industrial Design (Disain Industri).